Clinical and epidemiological characteristics of patients with uveitis in an emergency eye care center in Brazil - Camilo,Eduardo Nery Rossi (2014)
Purpose: To analyze the clinical and epidemiological characteristics of patients with uveitis in an emergency eye care center. Methods: We conducted a prospective, observational study of patients with active uveitis admitted between May 2012 and July 2012 to an emergency eye care center. Results: The majority of patients were male (63.2%), with a mean age of 43.2 years; 66.2% patients were of mixed ethnicity, 22.5% were Caucasian, and 11.3% were black. Anterior uveitis was observed in 70.1% patients, posterior uveitis in 26.5%, and panuveitis in 3.4%; no patient was diagnosed with intermediate uveitis. All patients had a sudden and acute presentation. The most frequent symptoms were ocular pain (76.9%), redness (59.8%), and visual blurring (46.2%). The majority of patients had unilateral disease (94.9%) with a mean symptom duration of 6.2 days. Diffuse and anterior uveitis were associated with ocular pain (p<0.001). Scotomata and floaters were more frequent in patients with posterior uveitis (p=0.003 and p=0.016, respectively). Patients with anterior uveitis presented with better visual acuity (p=0.025). Granulomatous keratotic precipitates were more frequent in patients with posterior uveitis (p=0.038). An etiological diagnosis based on the evaluation at the emergency center was made in 45 patients (38.5%). Conclusions: Acute anterior uveitis was the most frequent form of uveitis. Initial patient evaluation provided sufficient information for deciding primary therapy and aided in arriving at an etiological diagnosis in a considerable number of patients.